Does inflation targeting matter? - Manfred J. M. Neumann; Jürgen von Hagen (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
This paper studies the inflation and interest rate performances since the late 1970s for six former highinflation countries that adopted inflation targeting (IT) in the early 1990's. Using Germany, Switzerland and the US for comparison, we look at various aspects of central bank performance in a pre-IT period (1978-92) and a post-IT period (1993-01). The results of all types of evidence considered uniformly lead to the general conclusion that IT has proven a useful strategy for reducing the level and volatility of inflation. However, IT central banks did not outperform the central banks used as reference cases during the second period. We then present an event study of monetary policy comparing inflation and interest rate developments after the 1978 and the 1998 oil price shocks. Here we find that IT central banks realized significantly larger gains in credibility than the central banks in the reference group. . This result corroborates the conclusion that IT is a useful framework for communicating a monetary policy strategy aiming at low inflation rates.
Keywords: 330; Inflation Targeting; Taylor-Regel; Wirkungsanalyse; Inflationsbekämpfung; Glaubwürdigkeit; Welt